Selective feticide in dichorionic diamniotic (DCDA) twins complicated with previable premature rupture of membrane before 24 weeks may be a safe therapeutic alternative to ongoing pregnancy - Caixia Zhu; Haiyan Liu; Hui Zhu; Linhuan Huang (BMC, 2024)
Abstract Background To date, there are no clinical guidelines for dichorionic diamniotic (DCDA) twins complicated with previable premature rupture of membrane (PV-ROM) before 24 weeks of gestation. The typical management options including expectant management and/or pregnant termination, induce the risks of fetal mortality and morbidity. Objective To explore the feasibility selective feticide in DCDA twins complicated with PV-ROM. Study design A Retrospective cohort study, enrolling 28 DCDA twins suffering from PV-ROM in a tertiary medical center from Jan 01 2012 to Jan 01 2022. The obstetric outcome was compared between selective feticide group and expectant management group. Results There were 12 cases managed expectantly and 16 underwent selective feticide. More cases suffered from oligohydramnios in expectant management group compared to selective feticide group (P = 0.008). Among 13 cases with ROM of upper sac, the mean gestational age at delivery was (33.9 ± 4.9) weeks in the selective feticide group, which was significantly higher than that in the expectant management (P = 0.038). Five fetuses (83.3%) with selective feticide delivered after 32 weeks, whereas only one (14.3%) case in expectant management group (P = 0.029). However, in the subgroup with ROM of lower sac, no significant difference of the mean gestation age at delivery between groups and none of cases delivered after 32 weeks. Conclusion There was a trend towards an increase in latency interval in DCDA twins with PV-ROM following selective feticide, compared to that with expectant management. Furthermore, selective feticide in cases with PV-ROM of upper sac has a favorable outcome.